KARAKTERISTIK SUMBERDAYA ALAM DAN RENCANA PENGELOLAAN DAS TIWORO KABUPATEN MUNA BARAT - Hasddin, Hasddin (EDUTECH CONSULTANT, 2019)
This study aims to determine the actual conditions (characteristics) of Tiworo watershed natural resources. The results showed that in the Tiworo watershed the average rainy day was around 8 days per month where March, April, May and December were the months with the most rainy days (12 rainy days) with an average of 81 mm with the highest rainfall occurring at April with an intensity of 155 mm. The topography of the Tiworo watershed area is generally flat (65.02%) and gentle (21.55%). Based on the flow, the Tiworo watershed is in parallel or combination, while the shape of the flow pattern is parallel. The Tiworo watershed area generally has a severe erosion hazard level with an area of ​​21,624.22 ha or 66.26% of the total watershed area. Land use in the widest area of ​​the Tiworo watershed is mixed farms of around 6,939.54 (21.26%) and moorings which reach 6,296.58 ha (19.29%), while forest vegetation land only reaches 4,931.12 Ha (15.11%) consisting of from primary forest, mangrove forest, secondary forest, and mangrove forest. General erosion (low, medium, high and very high) was 57% or already worrying. The results of the study also show that the existing resources in the Tiworo watershed area are; a) Agriculture and plantations; b) Freshwater fisheries, c) Forestry; and d) Ecotourism. From the existing natural resources characteristics, a comprehensive and integrated management of the Tiworo watershed is needed which is carried out through stages a) planning; b) implementation; c) monitoring and evaluation; and d) guidance and supervision.